Sad Historian. Issue 4 (24th January 2023) - Steedman, Carolyn
Abstract: William Godwin's history writing and Oliver Goldsmith's poetry are used to explore the visual turn in history writing and the historian's project of "rescuing" the poor and dispossessed of the past.